Penerapan Etika Bisnis Islam (Studi Kasus Pada PT. Bank Syariah Indonesia KCP Setia Budi Kota Medan - Basithul Armi; Riyan Pradesyah (Yayasan Rahmat Islamiyah, 2022)
Islamic Business Ethics is a norm sourced from the Al-Quran and Hadith which is used as a guide for acting, behaving, and behaving as well as distinguishing which is good and bad in conducting business activities. Business cannot be separated by ethics, and business cannot be separated from human life, even business is a popular activity in human daily life. In essence, ethics is an integral part of a business that is run professionally. This study aims to determine the application of Islamic business ethics at Bank Syariah Indonesia KCP Setia Budi Medan. The method used in this study is a qualitative method, namely data collection techniques by means of observation, interviews, and documentation. The results of this study, business ethics in Indonesian Islamic Banks have been implemented, this can be seen from the absence of an element of Riba in the operations of Indonesian Islamic banks. The business ethics applied in Indonesian Islamic banks have been implemented in accordance with Islamic business ethics, this can be seen from the honesty of the employees regarding the trust given to make transactions in accordance with the Fatwa of the National Sharia Council.